Darolutamide is a potent androgen receptor antagonist with strong efficacy in prostate cancer models. Issue 5 (23rd March 2019) - Sugawara, Tatsuo; Baumgart, Simon J.; Nevedomskaya, Ekaterina; Reichert, Kristin; Steuber, Holger; Lejeune, Pascale; Mumberg, Dominik; Haendler, Bernard
Abstract : Darolutamide is a novel androgen receptor (AR) antagonist with a distinct chemical structure compared to other AR antagonists and currently in clinical Phase 3 trials for prostate cancer. Using cell‐based transactivation assays, we demonstrate that darolutamide, its diastereomers and its main metabolite keto‐darolutamide are strong, competitive antagonists for AR wild type, and also for several mutants identified in prostate cancer patients for which other AR antagonists show reduced antagonism or even agonism. Darolutamide, its two diastereomers and main metabolite are also strong antagonists in assays measuring AR N/C interaction and homodimerization. Molecular modeling suggests that the flexibility of darolutamide allows accommodation in the W742C/L mutated AR ligand‐binding pocket while for enzalutamide the loss of the important hydrophobic interaction with W742 leads to reduced AR interaction. This correlates with an antagonistic pattern profile of coregulator recruitment for darolutamide. In vitro efficacy studies performed with androgen‐dependent prostate cancer cell lines show that darolutamide strongly reduces cell viability and potently inhibits spheroid formation. Also, a marked down‐regulation of androgen target genes paralleled by decreased AR binding to gene regulatory regions is seen. In vivo studies reveal that oral dosing of darolutamide markedly reduces growth of the LAPC‐4 cell line‐derived xenograft and of the KuCaP‐1 patient‐derived xenograft. Altogether, these results substantiate a unique antagonistic profile of darolutamide and support further development as a prostate cancer drug. Abstract : What's new? Comparison of genomic landscapes from primary prostate cancer and metastatic tumor shows that resistance mechanisms are centered on androgen signaling and increased synthesis. Here, the novel androgen receptor (AR) antagonist darolutamide shows strong in vitro and in vivo efficacy in different prostate cancer models. Darolutamide retains its antagonistic properties at elevated androgen levels and for several AR mutants identified in therapy‐resistant patients. A unique binding profile inside the AR ligand‐binding domain linked to the flexibility of darolutamide is proposed. Altogether, these results substantiate a unique antagonistic profile of darolutamide and support further development as a prostate cancer drug.